Impact of clinical pharmacist on medication adherence among psoriasis patients: A randomized controlled study - Aishwarya C. Hiremath; Ramesh Bhandari; Shashikala Wali; M.S. Ganachari; Bhavana Doshi (Elsevier, 2021)
Background: Psoriasis is a chronic inflammatory disease and requires long term management due to which patients become non-adherent to the therapy. Hence this study aims to assess the impact of clinical pharmacists to improve medication adherence in patients with psoriasis. Materials and methods: This is a randomized controlled study conducted at a tertiary care teaching hospital in the dermatology department, among 68 patients. Aged 18-65 years from the outpatient department diagnosed with psoriasis disease and on treatment were enrolled in the study. Patients with multiple co-morbidities like HIV, hepatitis B/C, and vulnerable populations like lactating and pregnant women are excluded from the study. Enrolled patients are then randomized after taking the Informed consent form. The interventional groups of patients were provided with a patient information leaflet and pharmacist education and counselling along with standard care. Medication adherence of the patients was evaluated at the baseline level to the follow-up after 1 month. Results: Total of 68 were enrolled in the study, out of which 63 completed the study. There was no difference observed at the pre-test in both the groups. After the intervention, there was a significant difference in the experimental group after post-test (U = 200.00, p = 0.0001). Adherence was improved in the experimental group. Conclusion: There is a need for clinical pharmacists in providing the patients with knowledge about long term disease management like psoriasis. The implement of specialty pharmacists in dermatological disorders is an excellent choice to address the unattended needs of the patient.